Association of methylene tetrahydrofolate reductase gene mutation in unexplained recurrent pregnancy loss - Sultana, Masuda; Banu, Ferdous Ara; Chowdhury, Sanjukta; Bul-Bul, Surayea; Parveen, Tabassum; Begum, Firoza (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Recurrent pregnancy loss (RPL) without apparent causative factor which may be identified in about 50% of cases known as unexplained recurrent pregnancy loss. RPL is very distressing and can be heartbreaking for the couple. Among the many causes of RPL Methylene Tetrahydrofolate Reductase (MTHFR) gene mutation have been postulated as a possible cause. Aim of the study was to assess the association of methylene tetrahydrofolate reductase gene mutation (C677T and A1298C) in unexplained recurrent pregnancy loss. Methods: This was a case-control study conducted at the Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh from May 2020 to April 2021. A total of 34 patients with unexplained recurrent pregnancy loss (RPL) and 34 age and BMI-matched controls were selected as study subjects. Data was analyzed using SPSS software, version 22.0. Results: The frequency of heterozygous mutant genotype of MTHFR C677T and A1298C was statistically significantly higher in the case group than the control (38.2% vs 5.9%, p=0.001 and 55.9% vs 11.8%, p=0.000 respectively). No homozygous mutation for MTHFR C677T and only 1 for A1298C in the case group was found. The mutant T allele for MTHFR C677T and Mutant C allele for A1298C were found more frequently in cases compared to the controls (19.1% vs. 2.9% and 30.9% vs. 5.9%). Both the differences were statistically significant (p=0.003 and 0.000 respectively). Compound heterozygous mutant genotype CT/AC was found in 20.6% of RPL patients and not was found in the control. Conclusions: MTHFR C677T and A1298C mutations pose a risk for unexplained recurrent pregnancy loss (RPL). Individuals with these mutations and a history of recurrent pregnancy loss may benefit from tailored management strategies, including low dose aspirin and low molecular weight heparin, to address potential risks.